(3GdMHd GdhKjb aj fUQI GdUOjbs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai hHYO abO QaY Edj SDGd aj bhdg JYGdi dG jUdGgG EdG GdCTbi GdPj cPH hJhdi hSjLfHgG GdCJbi hgd GdeQGO HGdCJbi CHh HcQ GdUOjb s
(3BNQgG (B:s
(3BJ Pdc GdCaVd ef GdCeI EeG CHh HcQ hEeG Ydi hKHJ Cf GdBjI ZjQ UGdMI dYdj jbf MedgG Ydi CHj HcQ hKHJ OdGdI GdBjI CjVG Ydi Cf CHG HcQ CaVd GdCeI GfJgi cdGe GdEJeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 /301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 629s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs